2021
DOI: 10.1186/s13071-021-04721-6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approach to support taxonomic species discrimination based on helminth collections data

Abstract: Background There are more than 300 species of capillariids that parasitize various vertebrate groups worldwide. Species identification is hindered because of the few taxonomically informative structures available, making the task laborious and genus definition controversial. Thus, its taxonomy is one of the most complex among Nematoda. Eggs are the parasitic structures most viewed in coprological analysis in both modern and ancient samples; consequently, their presence is indicative of positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Measurements of Pearsonema eggs were made using a digital image analysis system (Microimage 4, Microsoft Corp.) at 400× magnification following Borba et al (2021) . The measurements were performed on 25 undamaged eggs, selected regardless of their study area of origin.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of Pearsonema eggs were made using a digital image analysis system (Microimage 4, Microsoft Corp.) at 400× magnification following Borba et al (2021) . The measurements were performed on 25 undamaged eggs, selected regardless of their study area of origin.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, C. hepaticum eggs from Meriones persicus and R. rattus are described as having a ‘very peculiar morphology’, that is, a punctuated and a radial eggshell ornamentation, with a thick eggshell (5.54 μm) (Borba et al ., 2021b). Furthermore, Borba et al (2021b) recently reported a new methodology for Capillariid species identification based on artificial intelligence technology. In this case, despite having taken the measurements of the two mucoid polar opercula, the discriminant analysis between representatives of Capillariidae was carried out using only the length and width of the eggs as measurements (Borba et al ., 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Borba et al (2021b) recently reported a new methodology for Capillariid species identification based on artificial intelligence technology. In this case, despite having taken the measurements of the two mucoid polar opercula, the discriminant analysis between representatives of Capillariidae was carried out using only the length and width of the eggs as measurements (Borba et al ., 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations